Modulation of Global Gene Expression by Aneuploidy and CNV of Dosage Sensitive Regulatory Genes. - Zhang, S.; Wang, R.; Huang, C.; Zhang, L.; Sun, L. (Genes, 2021)
Aneuploidy, which disrupts the genetic balance due to partial genome dosage changes, is usually more detrimental than euploidy variation. To investigate the modulation of gene expression in aneuploidy, we analyzed the transcriptome sequencing data of autosomal and sex chromosome trisomy in Drosophila. The results showed that most genes on the varied chromosome (cis) present dosage compensation, while the remainder of the genome (trans) produce widespread inverse dosage effects. Some altered functions and pathways were identified as the common characteristics of aneuploidy, and several possible regulatory genes were screened for an inverse dosage effect. Furthermore, we demonstrated that dosage changes of inverse regulator Inr-a/pcf11 can produce a genome-wide inverse dosage effect. All these findings suggest that the mechanism of genomic imbalance is related to the changes in the stoichiometric relationships of macromolecular complex members that affect the overall function. These studies may deepen the understanding of gene expression regulatory mechanisms.